Strengthening the Quality of Ma'had Aly Graduates through Optimizing Management of Infrastructure Facilities and Lecturer Competencies - Badrudin Badrudin; Enjang Yusuf Ali; Moh. Sulhan; Ulfah Nurul Badriyatul Fitri (Institut Agama Islam Negeri (IAIN) Curup, 2021)
The main problem of this study is the unoptimal infrastructure management and lecturers' competence that impact on the low quality of Ma'had Aly Miftahul Huda Tasikmalaya graduates. This study is aimed to explain the quality strengthening of Ma'had Aly graduates through the optimization of infrastructure management and lecturer competence. Research on the quality of Ma'had Aly graduates has been carried out by other researchers as seen from the influence of lecturers' educational qualifications. This research is focused on investigating the influence of infrastructure management and lecturer competence in improving the quality of Ma'had Aly graduates. This study used a quantitative approach with a descriptive correlational method. The data analysis using product moment correlation analysis. The sample of this study was 50 students who graduated from 2019-2020 that were selected using proportional stratified random sampling. The results of the study concluded that strengthening the quality of Ma'had Aly's education graduates could be done through optimization of infrastructure management and lecturer competence. Infrastructure management has a significant effect on the quality of graduates by 23.4%; Lecturer competence has a significant influence on the quality of graduates by 7.96%; and Infrastructure management and lecturer competence simultaneously had a significant effect on the quality of Ma'had Aly's graduates by 45.7%.